Treatment of chronic subdural Hematoma with burr hole craniostomy and irrigation - Gurunathan, J (Indian Journal of Neurotrauma, 2005)
Several surgical procedures have been reported for the treatment of chronic subdural hematoma. Whether drain is required is not clear. Usefulness of burr hole craniostomy, irrigation and refilling the hematoma cavity with saline are analyzed. Between 1994 and 2004, 103 adult patients with chronic subdural hematoma were studied in respect to post operative recurrence and clinical improvement after burr hole irrigation without subdural drainage. Fifty six patients (54%) had definite history of head injury, and the hematoma was bilateral in 12 patients (11%). Ninety seven (94%) patients improved. Two patients required craniotomy and membranectomy after repeat irrigation. Recurrent bleeding from the outer membrane is the proven and widely accepted theory. Eosinophilic infiltration in the outer membrane may contribute the local hyperfibrinolysis and recurrent bleeding. Hematoma evacuation brings about hemostasis and fibrosis by stopping self-perpetuating cycles in the subdural neocapillaries. When neomembrane is matured, the neocapillary is no longer fragile. If absorption exceeds rebleeding the hematoma will disappear.
Keywords: Chronic subdural hematoma; hematoma recurrence; subdural air collection; subdural drainage